Pelaksanaan Fungsi Lembaga Kemasyarakatan Desa dalam Mewujudkan Pembangunan Desa di Desa Oematamboli Kecamatan Lobalain Kabupaten Rote Ndao (Pusat Riset dan Inovasi Nasional, 2026)
Village institutions play an important role in supporting participatory and sustainable rural development. The Village Law No. 6 of 2014 recognizes village autonomy and emphasizes the importance of community participation through Village Community Institutions (Lembaga Kemasyarakatan Desa/LKD). However, the implementation of these institutions in practice has not always functioned effectively. This study aims to analyze the role of village community institutions in supporting village development and to identify the factors that influence their effectiveness in Oematamboli Village, Lobalain District, Rote Ndao Regency. This research employs an empirical legal research method with a qualitative approach. Data were obtained through interviews and field observations involving village government officials, community institution administrators, and community leaders, while secondary data were obtained from documents and relevant regulations. The results indicate that the functions of LKD, including the Community Empowerment Institution (LPM), Neighborhood Associations (RT), and Community Associations (RW), have not been implemented optimally in supporting village development. This condition is reflected in the limited participation of LKD in development planning, weak absorption of community aspirations, and low community participation in development activities. Several factors influencing this condition include limited human resource capacity, inadequate infrastructure, low community participation, and limited development funding. Therefore, strengthening institutional capacity, improving coordination, and increasing community participation are necessary to enhance the effectiveness of village development.